(untitled) (One Health & Risk Management, 2021)
Introduction. Eating habits are formed in the first years of life and sometimes persist throughout lifetime. It is necessary to develop coherent nutritional educational programs to guide adolescents towards a healthy diet. Material and methods. The study was conducted on a group of 194 students from the ninth and the twelfth grade from Dimitrie Cantemir High School in Iasi. These young people were evaluated for their physical development with the help of body mass index and eating habits. Eating habits were assessed on the basis of a weekly food intake questionnaire. The processing of the results was carried out by the Pearson test. Results. Physical development was mainly at normal values (68.55%). There were 19.07% underweight students but also 12.37% young people with obesity. Milk was present in menus especially 2-3 times (35.05%) or 1 time (25.77%) per week, with insignificant differences by class and sex. Chicken meat was mainly consumed 2-3 times a week (42.78%) with insignificantly differing in classes, but significant in gender (p˂0.001). Vegetables were consumed especially 2-3 times (30.92%) per week or daily (28.35%). Sweets were consumed mainly on a daily basis (29.89%) or 2-3 times (26.28%) per week. Conclusions. The eating habits of students surveyed were different in girls than in boys, an aspect that draws attention to young females for whom identification with the current ideal of beauty is essential.